Long-term outcomes of dual innervation in functional muscle transfers for facial palsy. Issue 10 (October 2021) - Tzafetta, Kallirroi; Al-Hassani, Fawaz; Pinto-Lopes, Rui; Wade, Ryckie G.; Ahmad, Zeeshan
Summary: Background: This study describes a different approach with a 2-stage facial reanimation in patients with long-standing unilateral facial paralysis using free gracilis muscle transfer, innervated by both cross-facial nerve graft and masseteric nerve. The authors present their rationale, surgical technique, and long-term outcomes. Methods: Between August 2012 and March 2016, 11 patients (6 female and 5 male patients) underwent a 2-staged dually innervated gracilis muscle transfer. Patients were evaluated with physical examination and needle electromyography. A standardized assessment of preoperative and postoperative photographs and videos was performed using Terzis' smile functional grading system at 48 months following surgery and the Emotrics software to assess improvement in symmetry over a 36-month postoperative period. Results: Voluntary contraction of the gracilis muscle was observed in all patients at a mean of 4 months and 4 days following muscle transfer. A spontaneous smile produced without teeth clenching was developed in all patients by 18 months postoperatively. Six patients achieved excellent and 5 good results. The difference between the averaged pre- and postoperative scores was statistically significant. With Emotrics, there were significant improvements in the smile angle, upper lip elevation, commissural excursion, and commissural height, with continuous improvement over 36 months. The postoperative electromyography (EMG) confirmed dual innervation of the gracilis muscle by the facial and masseteric donor motor neural sources. We present our results at minimum 48 months postoperatively. Conclusions: Dual innervated two-stage gracilis transfer is an effective method for reanimation in long-standing unilateral facial paralysis, providing both rapid reinnervation of the transferred muscle, together with a powerful, synchronous smile.